Influence of Imperfect Contact Condition on Dispersion of Axisymmetric Waves in Bi-Layered Hollow Cylinder with Inhomogeneous Initial Stresses - Akbarov, S. D.; Bagirov, E. T.; Ipek, C. (SPRINGER, 2024)
The influence of the shear-spring type imperfect contact conditions between the layers of the bi-layered hollow cylinder with inhomogeneous initial stresses on the dispersion of the axisymmetric waves propagating in this cylinder is studied. It is assumed that the inhomogeneous initial stresses in the cylinder are caused by the hydrostatic pressure acting in the interior of the cylinder before the wave starts to propagate. The corresponding dynamic problem is studied within the framework of the piecewise homogeneous body model by utilizing the three-dimensional linearized theory of the elastic waves in initially stressed bodies. The discrete-analytical solution method is employed to solve the corresponding eigenvalue problem. Numerical results on the influence mentioned above are presented and discussed. It is established that the significant effect of the imperfection of the contact conditions is observed on the dispersion curves related to the new type modes caused by the mentioned imperfection.
Keywords: inhomogeneous initial stresses; wave dispersion; imperfect contact conditions; Mechanics